Role of International Accounting Standard in Improving Accounting Processes in Grants and Aid / Comparative Study - رؤى حسين عبد الحسين (Journal of Madenat Alelem University College, 2018)
Imposed the current environment the application of international accounting standards and in particular the IAS (20) in all foreign and local companies, in order to provide useful information. It is known that the grants and aid are processed in accordance with the accounting system standardized and government accounting system and which do not provide useful information , so it should be on economic units Application of International Accounting Standard (20) for the purpose of improving the special grants accounting treatments and aid and how to view them in the financial statements . And the search may come to many of the most important conclusions that the application of I International Accounting Standard (20) contribute to the improvement of accounting treatments for grants and aid and how to view them in the financial statements. And research has reached many of the recommendations should be the most important economic units of public and private application of International Accounting Standard (20) in order to improve the accounting treatments for grants and aid nd how to view them in the financial statements